Correction: Twists or turns: stabilising alpha vs. beta turns in tetrapeptides. Issue 28 (10th July 2020) - Hoang, Huy N.; Hill, Timothy A.; Ruiz-Gómez, Gloria; Diness, Frederik; Mason, Jody M.; Wu, Chongyang; Abbenante, Giovanni; Shepherd, Nicholas E.; Fairlie, David P.
Abstract : Correction for 'Twists or turns: stabilising alpha vs. beta turns in tetrapeptides' by Huy N. Hoang et al., Chem. Sci., 2019, 10, 10595–10600, DOI: ; 10.1039/C9SC04153B .